Cost effective treatment of uncomplicated gonorrhoea including co-infection with Chlamydia trachomatis - (:unkn) unknown (ADIS INTERNATIONAL LTD, 1997)
We evaluated the cost effectiveness of treating uncomplicated gonorrhoea in a theoretical cohort of 1000 adults (nonpregnant women of reproductive age, or men) with either intramuscular ceftriaxone 125mg or a single oral dose of cefixime 400mg, ofloxacin 400mg or ciprofloxacin 500mg. We assumed that all patients were also empirically treated for uncomplicated chlamydial infection, with either a single oral dose of azithromycin 1g, or oral doxycycline 100mg twice daily for 7 days. Treatment of gonorrhoea with intramuscular ceftriaxone was found to be the most cost-effective alternative. This was followed by treatment with the either of the fluoroquinolones (ofloxacin or ciprofloxacin), then cefixime. For empirical treatment of uncomplicated chlamydial infection, doxycycline was more cost effective than azithromycin when approximately more than 80% of the patients were assumed to comply with the doxycycline regimen. When patients' compliance was poor with the doxycycline regimen, the azithromycin therapy became more cost effective from a societal viewpoint. Nevertheless, its relatively high cost to the individual patient with limited financial resources might prevent him or her from filling prescriptions. Any decrease in patients' compliance with the azithromycin therapy would favour treatment with doxycycline.
Keywords: PELVIC INFLAMMATORY DISEASE; NEISSERIA-GONORRHOEAE; WOMEN; AZITHROMYCIN; CEFTRIAXONE; PREVALENCE; THERAPY; RISK; CARE; MEN